The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/jnr.24676
|View full text |Cite
|
Sign up to set email alerts
|

In vivo microstimulation with cathodic and anodic asymmetric waveforms modulates spatiotemporal calcium dynamics in cortical neuropil and pyramidal neurons of male mice

Abstract: Electrical stimulation has been critical in the development of an understanding of brain function and disease. Despite its widespread use and obvious clinical potential, the mechanisms governing stimulation in the cortex remain largely unexplored in the context of pulse parameters. Modeling studies have suggested that modulation of stimulation pulse waveform may be able to control the probability of neuronal activation to selectively stimulate either cell bodies or passing fibers depending on the leading polar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 111 publications
8
47
1
Order By: Relevance
“…Neither PW, nor polarity, wave asymmetry or interphase intervals were varied in this study ( Stieger et al, 2020 ). We thus cannot claim our systematic investigation of different STN-DBS parameters in the hemi-parkinsonian rat to be complete, yet we were already able to show that the transiently induced rotation behavior provides a valuable readout to assess DBS parameters in the hemi-PD rat.…”
Section: Discussionmentioning
confidence: 85%
“…Neither PW, nor polarity, wave asymmetry or interphase intervals were varied in this study ( Stieger et al, 2020 ). We thus cannot claim our systematic investigation of different STN-DBS parameters in the hemi-parkinsonian rat to be complete, yet we were already able to show that the transiently induced rotation behavior provides a valuable readout to assess DBS parameters in the hemi-PD rat.…”
Section: Discussionmentioning
confidence: 85%
“…Monophasic waveforms are more efficacious than conventional charge-balanced biphasic pulses [53,54] and asymmetric waveforms can be used to modulate the spatial selectivity for neuronal stimulation. [55] However, charge imbalance of monophasic pulses and the long activation phase of asymmetric pulses might result in irreversible Faradaic reactions that can damage the electrode and the tissue. Application of PEDOT:PSS opens the possibility to employ alternative waveforms without adverse effects, which possibly improves desired stimulation effects and therapeutic outcomes.…”
Section: Besides Lipid Peroxidation Rems Et Al Recently Demonstratedmentioning
confidence: 99%
“…[ 57 , 58 ] Using in vivo two‐photon calcium imaging in mice, rats, and cat models, Histed et al revealed a sparse, distributed population of cortical neurons by electrical microstimulation via glass pipettes containing tungsten and platinum–iridium microwire electrodes. [ 59 ] In more recent studies, the Kozai and coworkers utilized mesoscale fluorescence microscopy and two‐photon imaging to investigate the calcium responses to prolonged electrical stimulation in Thy1‐GCaMP6s mice and reported the effect of stimulation frequency, [ 60 ] pulse symmetry, and phase order, [ 61 ] using Michigan planar arrays. [ 62 ] These studies demonstrate the capability of fluorescence imaging to characterize the neuronal response to stimulation at cellular and mesoscopic spatial scales in vivo.…”
Section: Introductionmentioning
confidence: 99%